Association of Androgen Deprivation Therapy with Cerebral Small Vessel Disease Burden in Prostate Cancer - Longhai Zeng; Rentang Bi; Zijun Yang; Qian Liu; Yanmei Qiu; Yanhao Wei; Haokun Peng; Wenbin Xiong; Bo Hu; Ya'nan Li (Current Neuropharmacology, 2026)
Introduction: Androgen Deprivation Therapy (ADT) is essential for advanced Prostate Cancer (PCa) but may increase cardiovascular and cerebrovascular risks. Its adverse effects on cerebral small vessels remain unclear. Leukoaraiosis (LA) and Lacunar Infarction (LI) are neuroimaging markers of Cerebral Small Vessel Disease (CSVD) associated with cognitive decline and stroke. materials and methods: Study Population This study utilized data from the SMART cohort, which includes patients at 13 public tertiary hospitals in Hubei Province, Central China (≈150 million population) who had brain MRI for cerebral small vessel disease (CSVD) research. The 13 hospitals are Wuhan Union Hospital (3 campuses), People's Hospital of Dongxihu, Hubei Provincial Hospital of Integrated Chinese and Western Medicine, and 8 others in Wuhan and Yichang. SMART cohort inclusion: age >18 years with brain MRI; exclusion: no informed consent, severe psychiatric disorders, or intracranial tumors interfering with CSVD evaluation. The study focused on prostate cancer patients from this cohort treated at the 13 hospitals during January 2014–January 2025.Baseline data were self-reported via standardized interviews by trained staff and stored as electronic medical records. Demographics, clinical traits (age, sex, systematically recorded height/weight, lifestyle, vascular risks, medical history, ICD-10-based diagnosis, medication use), and prostate cancer treatment info (for androgen deprivation therapy screening) were extracted.Approved by Huazhong University of Science and Technology’s Ethics Committee, registered at China Clinical Trial Registry (ChiCTR2200061036), and compliant with STROBE. Datasets are available from the corresponding author on request.It is important to note that this is a hospital-based population, and thus our findings are primarily generalizable to men with PCa in secondary care settings, who likely have a higher baseline burden of cerebrovascular risk factors.​ Androgen-deprivation therapy exposure  PCa patients who started ADT of any kind within 1 year of diagnosis were considered exposed to ADT. ADT drugs that met the inclusion criteria included antiandrogens (Bicalutamide, Flutamide, Enzalutamide, and Abiraterone), GnRH agonists (Leuprolide, flutamide, enzalutamide, and abiraterone), Goserelin and Triptorelin) and bilateral orchiectomy. Groups were grouped according to whether ADT was used or not. Patients who started ADT more than 1 year after diagnosis were excluded to avoid inclusion of patients with recurrent or metastatic disease. Patients with previous histories of myocardial infarction (MI), atherosclerosis, or stroke were excluded from all analyses of the primary outcome. Neuroimaging Analysis The MRI protocol includes at least the following sequences: T2-weighted fluid-attenuated inversion recovery (FLAIR), and T2-weighted imaging. Experienced and trained raters, blinded to clinical details, performed the analyses with the use of prespecified scoring tables. Leukoaraiosis and lacunar infarction were assessed according to the Standards for Reporting Vascular Changes on Neuroimaging. The Fazekas scale was used to grade periventricular and deep WMHs. Experienced neurologists used image analysis software to manually measure the WMH in four different planes[14] , and the volume data of WMH in each plane were added to finally obtain the overall WMH volume. Outcomes The prespecified primary outcome was CSVD burden, defined as the incidence of leukoaraiosis or lacunar infarction. Secondary outcomes included the volume of WMHs, the severity and distribution of LA, and the etiology of LA. Statistical Analysis We described the baseline characteristics of the two main study groups using medians with interquartile ranges (IQR) for continuous variables and counts (percentages) for categorical variables. Categorical variables were compared using the χ2 test, and continuous variables were compared using the two-sample t test or the Mann-Whitney U test. Univariate and multivariate logistic regression models were used to analyze the association of ADT with CSVD burden (LA and lacunar infarction). In addition, univariate and multivariate multinomial regression models were fitted to explore the association between ADT exposure and LA etiology[14]. On the basis of the available evidence, we adjusted for potential confounders that could be associated with ADT burden and CSVD. A prespecified list of variables included age, sex, hypertension, diabetes, and baseline blood pressure. These variables were included in the multivariate model if they had a univariate association with p < 0.2. P < 0.05 was considered statistically significant. Methods: This retrospective analysis used data from the multi-center SMART cohort (13 hospitals, 2014-2025) to examine associations between ADT exposure and CSVD burden using multivariate logistic regression, with stratified analyses by treatment duration and modality. Mediation analysis assessed the statistical role of systemic inflammation. Results: PCa patients receiving ADT (n=210) had a significantly higher risk of LA (adjusted OR=1.59, 95% CI: 1.15-2.20) compared to non-ADT users (n=1,181), but no significant increase in LI risk was observed. In the statistical mediation analysis, the Systemic Inflammation Response Index (SIRI) accounted for 27.21% of the observed association between ADT and LA. A duration-dependent association was evident, with significantly elevated LA risks in patients receiving medium-long term (12-24 months) and long-term (>24 months) ADT. Discussion: These findings suggest that ADT is associated with increased cerebral small vessel injury, particularly LA. The duration-dependent association and the statistical association involving systemic inflammation are consistent with a potential pathway linking ADT to cerebrovascular damage, but causality cannot be inferred. Monitoring cerebrovascular health and inflammatory markers in patients on prolonged ADT may aid risk stratification. Conclusion: In this retrospective analysis of PCa patients without prior cardiovascular or cerebrovascular disease, ADT was associated with an increased burden of early LA in a duration-dependent manner, with systemic inflammation statistically accounting for part of this association.